2019
DOI: 10.1002/smi.2882
|View full text |Cite
|
Sign up to set email alerts
|

Fighting for time: Spillover and crossover effects of long work hours among dual‐earner couples

Abstract: Drawing upon the spillover-crossover model, this study examined the extent to which one's work time demands spilled over to the family domain and crossed over to his or her spouse, utilizing data of 365 dual-earner couples from the 500 Family Study. The results of the distinguishable actor-partner interdependence model indicated that there was gender symmetry in the spillover processes such that the effects of work hours were identical between men and women. Further, although there was more bidirectional cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 64 publications
3
23
0
Order By: Relevance
“…Another persisting problem is that of the time dedicated to household chores, which was perceived to be more important to the women in this study, confirming what other studies had already pointed out: that women play a double role [36,46], and that this has been exacerbated during the COVID-19 crisis [34]. However, perhaps one of the most interesting results of this research is the different perceptions of men and women regarding time spent on care, as the problem of workload in the home is shown to represent a difference in perception, with the man perceiving that while his partner traditionally spends more time on care, both spend an equal amount of time on care during confinement.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Another persisting problem is that of the time dedicated to household chores, which was perceived to be more important to the women in this study, confirming what other studies had already pointed out: that women play a double role [36,46], and that this has been exacerbated during the COVID-19 crisis [34]. However, perhaps one of the most interesting results of this research is the different perceptions of men and women regarding time spent on care, as the problem of workload in the home is shown to represent a difference in perception, with the man perceiving that while his partner traditionally spends more time on care, both spend an equal amount of time on care during confinement.…”
Section: Discussionsupporting
confidence: 91%
“…This confirmed that, in addition to the actual time spent, the mental burden, which results in more stress and a greater frequency of arguments, must be considered. These reflections support what other studies had already concluded (e.g., [36]), that this burden leads to higher stress, which can generate episodes of emotional crisis and depression among women. In addition, according to the results, women are more concerned about losing their jobs.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…These findings confirm the relevance of the work role for man’s identity [ 74 ], but it also expands the relevance of this role for both members of the couple. In fact, it has been reported that men’s main family role is being the breadwinner and their paid work is a way to prove their masculinity [ 99 ], more so in cultures with predominantly a traditional masculinity framing [ 100 ], as is the case in Latin American countries.…”
Section: Discussionmentioning
confidence: 99%